Thyridium lauri sp. nov. (Thyridiaceae, Thyridiales): a new pathogenic fungal species of bay laurel from Italy - Giuseppa Rosaria Leonardi; Dalia Aiello; Chiara Di Pietro; Antonio Gugliuzzo; Giovanna Tropea Garzia; Giancarlo Polizzi; Hermann Voglmayr (MycoKeys)
Laurus nobilis is an important Mediterranean tree and shrub native to Italy that is also commercially grown as spice and ornamental plant. Field surveys conducted since 2021 in Sicily (Italy) revealed that bay laurel plants in urban and private gardens and nurseries were severely affected by symptoms of stem blight and internal necrosis, which were associated with ambrosia beetle entry holes in the bark and internal wood galleries. The occurring ambrosia beetle was identified as Xylosandrus compactus, an invasive wood-boring pest previously reported from Sicily. Investigation of fungi from symptomatic tissues primarily resulted in the isolation of Thyridium-like colonies. The main symbiont of X. compactus, Ambrosiella xylebori, was also isolated from infested plants. Phylogenetic analyses of a combined matrix of ITS, LSU, act1, rpb2, tef1, and tub2 gene regions revealed that the isolated Thyridium-like colonies represent a new fungal species within the genus Thyridium. Based on both phylogeny and morphology, the new isolated fungus is described as Thyridium lauri sp. nov. Moreover, two recently described species, Phialemoniopsis hipposidericola and Phialemoniopsis xishuangbannaensis, are transferred to the genus Thyridium due to the confirmed synonymy of both genera, as supported by molecular phylogenies. Pathogenicity test conducted on potted plants demonstrated that T. lauri is pathogenic to bay laurel, causing internal necrosis and stem blight. The new species was consistently re-isolated from the symptomatic tissue beyond the inoculation point, thereby fulfilling Koch’s postulates. This study represents the first report of a new pathogenic fungus, T. lauri, causing stem blight and internal necrosis of bay laurel plants and associated with infestation of the invasive ambrosia beetle X. compactus.